The Impact of Diseases Experienced by Many Students on Learning Interests of STKIP Cultivation Binjai Students - Sitepu, Dewi Rulia; Afni, Khairina; Saputri, Lilis (Asian Journal of Applied Education (AJAE), 2023)
This study aims to see the relationship between the diseases experienced by students with their interest in learning. The type of research used in this research is descriptive qualitative research. The population of this study were all students in the first semester of each study program with the amount of data obtained as many as 178 people. Data collection techniques using a questionnaire / questionnaire. The results of this study are that there is an impact between the illnesses experienced by students and their interest in learning where illness can interfere with student learning concentration and can interfere with the continuity of student learning activities. The most common diseases experienced by students during the last 1 year were fever and stomach ulcers.